2017
DOI: 10.1017/s1368980017002531
|View full text |Cite
|
Sign up to set email alerts
|

Addressing barriers to exclusive breast-feeding in low- and middle-income countries: a systematic review and programmatic implications

Abstract: Objective: Despite numerous global initiatives on breast-feeding, trend data show exclusive breast-feeding (EBF) rates have stagnated over the last two decades. The purpose of the present systematic review was to determine barriers to exclusive breast-feeding in twenty-five low-and middle-income countries and discuss implications for programmes. Design: A search of Scopus, MEDLINE, CINAHL and PsychINFO was conducted to retrieve studies from January 2000 to October 2015. Using inclusion criteria, we selected bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
141
1
9

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(189 citation statements)
references
References 85 publications
20
141
1
9
Order By: Relevance
“…This effect was seen in Phnom Penh but did not reach statistical significance in the regression model when other variables were taken into account. Caesarean delivery is a commonly reported barrier to breastfeeding in LMIC (Kavle et al, ; Patel et al, ; Takahashi et al, ) but is not always found to increase likelihood of early BMS use, especially if the caesarean delivery is an emergency procedure rather than elective (Zanardo et al, ). Our survey did not distinguish between emergency and elective or planned caesarean deliveries, which may help explain the absence of association with BMS feeding in Phnom Penh.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect was seen in Phnom Penh but did not reach statistical significance in the regression model when other variables were taken into account. Caesarean delivery is a commonly reported barrier to breastfeeding in LMIC (Kavle et al, ; Patel et al, ; Takahashi et al, ) but is not always found to increase likelihood of early BMS use, especially if the caesarean delivery is an emergency procedure rather than elective (Zanardo et al, ). Our survey did not distinguish between emergency and elective or planned caesarean deliveries, which may help explain the absence of association with BMS feeding in Phnom Penh.…”
Section: Discussionmentioning
confidence: 99%
“…Among mothers in this study, concerns about insufficient or delayed milk supply were commonly cited reasons for introducing BMS. The high prevalence of these concerns is also evidenced by a 2017 systematic review conducted across LMIC (Kavle, LaCroix, Dau, & Engmann, 2017). Support and appropriate education on infant behaviour and cues from health professionals can aid in improving breastfeeding outcomes in developing country contexts (Imdad, Yakoob, & Bhutta, 2011;Khanal, Lee, Karkee, & Binns, 2015;Lou et al, 2014).…”
Section: Breastfeeding Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…All study materials, including IDI guides, observation guides and job aids, were designed based on a review of barriers to EBF and associated literature from low-and middle-income countries [8,16,17] and were pre-tested and adapted to the local context prior to implementation. The study team conducted the pre-test in the District of Rapale, Nampula Province, a rural area, similar in profile to other study sites, which was selected due to its vicinity to the Provincial Capital of Nampula City.…”
Section: Data Collectionmentioning
confidence: 99%
“…Lactating women may experience challenges to maintaining EBF for the first six months of an infant's life, as demonstrated in a recent systematic review which identified sixteen barriers to EBF including maternal perceptions of insufficient breastmilk, early introduction of foods and liquids prior to six months of age, and lack of counseling on physical breast problems. Yet, these barriers are often not adequately addressed through infant and young child feeding (IYCF) programs and initiatives, and further, are not reflected in country investments and access to skilled lactation support [8,9].…”
Section: Introductionmentioning
confidence: 99%